Factors Influencing Stakeholders’ Perception Towards Innovation on Halal Management Practices. - Md Lezal, Nur Adibah; Azizan, Anim Zalina (Research in Management of Technology and Business, 2026)
For this study, the Halal Malaysia is growing rapidly due to the technology advancements, but the perceptions of the stakeholders is an important factor in adoption of innovation. For the purpose of this study, to assess factors that influence the perceptions of stakeholders towards innovation in the management practices of halal management, the purpose framework is guided by Technology Acceptance Model (TAM), which emphasize Perceive Usefulness, Perceive Ease of Use, Trust and Perceive Enjoyment. For the purpose of this study, the populations included halal stakeholder in the state of Malacca, and the sampling technique involve the use of cross-sectional survey of 161 respondents.